UPAYA PENINGKATAN MINAT BACA MELALUI PERINTISAN RUMAH BACA â€œABDIâ€ DAN PENDAMPINGAN BELAJAR DARI MAHASISWA UNTUK DESA MENDALO INDAH - Yesi Nursofia Nursofia; Emi Efrini Efriani; Anisya Persi Persi; Monic Sri Cahnia; Yuliawati Yuliawati (IKIP SILIWANGI, 2021)
The pioneering of the ABDI reading house (Asri, Baca and Inspirasi) was based on the low interest in reading students' books. Mendalo Indah Village, which is a village close to Jambi University, does not yet have a reading house. In addition, the Covid-19 pandemic has overwhelmed parents of students to teach their children, especially with relatively low mastery of technology. ABDI Reading House, as a form of student and lecturer concern for the surrounding environment, is here to provide solutions to the problems of reading interest and the needs of parents for their children's learning assistance. This program is implemented by a community service team from the Pharmacy Student Association of the Faculty of Medicine and Health Sciences in collaboration with lecturers. The Village Head of Mendalo Indah provides a house to be used as a reading house and is supported by the provision of reading houses by funding from Jambi University through the Village Development and Empowerment Holistic Program (PHP2D). Learning assistance is carried out every day offline according to community demand by establishing health protocols and learning is carried out interactively with the play while learning method. This dedication has given birth to reading houses with various facilities and an increase in the number of visits to reading houses. The community feels very helped by the presence of the ABDI reading house in Mendalo Indah Village.